Preference of RIG-I for short viral RNA molecules in infected cells revealed by next-generation sequencing - Baum, Alina (National Academy of Sciences, 2010)
Intracellular detection of virus infections is a critical component of innate immunity carried out by molecules known as pathogen recognition receptors (PRRs). Activation of PRRs by their respective pathogen-associated molecular patterns (PAMPs) leads to production of proinflamatory cytokines, including type I IFN, and the establishment of an antiviral state in the host. Out of all PRRs found to date, retinoic acid inducible gene I (RIG-I) has been shown to play a key role in recognition of RNA viruses. On the basis of in vitro and transfection studies, 5′ppp RNA produced during virus replication is thought to bind and activate this important sensor. However, the nature of RNA molecules that interact with endogenous RIG-I during the course of viral infection has not been determined. In this work we use next-generation RNA sequencing to show that RIG-I preferentially associates with shorter, 5′ppp containing viral RNA molecules in infected cells. We found that during Sendai infection RIG-I specifically bound the genome of the defective interfering (DI) particle and did not bind the full-length virus genome or any other viral RNAs. In influenza-infected cells RIG-I preferentially associated with shorter genomic segments as well as subgenomic DI particles. Our analysis for the first time identifies RIG-I PAMPs under natural infection conditions and implies that full-length genomes of single segmented RNA virus families are not bound by RIG-I during infection.